Immunoisolation: where regenerative medicine meets solid organ transplantation. (September 2012) - Pareta, Rajesh; Sanders, Brian; Babbar, Paurush; Soker, Tom; Booth, Christopher; McQuilling, John; Sivanandane, Sittadjody; Stratta, Robert J; Orlando, Giuseppe; Opara, Emmanuel C
Immunoisolation refers to an immunological strategy in which nonself antigens present on an allograft or xenograft are not allowed to come in contact with the host immune system, and it is implemented to prevent allorecognition and avoid immunosuppression. In this setting, the two most promising technologies, encapsulation of pancreatic islets (EPI) and immunocloaking (IC), are used. In the case of EPI, islets are inserted in capsules that, allow exchange of oxygen, nutrients and other molecules. In the case of IC, a natural nanofilm is injected prior to renal transplantation within the vasculature of the graft with the intent to pave the inner surface of the vascular lumen and camouflage the antigens located on the membrane of endothelia cells. Significant progress achieved in experimental models is leading EPI and IC to clinical translation.